Information Distribution Service of Tourism and Creative Industry Using Mobile Application Technology - Deden A Wahab; Eko Budi Setiawan; Rahma Wahdiniwaty (IJNMT (International Journal of New Media Technology), 2017)
Creative industries and tourism is one sector that is easiest to improve the condition of the economy of a region. This study discusses the information distribution service usage model of mobile application technology using Location Based Service (LBS) and Global Positioning System (GPS) in the development of creative industries through integration with products of tourist destinations. By using the technology of location based services and global positioning system that will be developed and implemented on the application of geographic information systems and web-based mobile android, then the those creative industries would be material and guidance in utilizing information technology as a means to promote the business of creative industries it has to be more effective and efficient